An Analysis Of Inflectional Morpheme In The Articles Of Tempo English Magazine - Ni Putu Dewina Ratna Putri; Ayomi, Putu Nur (Journal of Language and Applied Linguistics, 2025)
The aim of this research is to find the kinds of inflectional morphemes and analyze the morphological process of new word formations in English by using articles of Tempo English Magazine. The more specific objective of this research is to know the structure (morphological process) word formation which involves the English inflectional morphemes. This research used the theory proposed by Fromkin, Rodman, & Hyams (2011). The method of this research used descriptive qualitative and quantitative. The data source of this research was from one of the famous digital magazines that is Tempo English Magazine. This research result shows that there are seven types of inflectional morphemes such as third person singular present (-s attached to verbs) with a percentage 8,20%, plural ( -s indicator of plural forms of nouns) 22,13%, possessive ( -s’ marks of possessive forms of nouns) 1,64%, progressive (-ing indicates the present participle)18,03%, past tense (-ed indicator of past tense of verbs) 48,36%, past participle (-en) 0,82%, and superlative (-est indicator of superlative form of adjectives) 0,82%. Keywords: inflectional, morpheme, morphological process